Reflection of Consonant Phonemes /b/ dan/d/ in Toba Batak Language into /p/dan /t/ in Angkola Batak Language - Alika Sandra Hasibuan; Dwi Widayati; Dardanila Dardanila (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The aim of this research was to describe the reflection of consonant phonemes /b/ and /d/ in Toba Batak language into /p/ and /t/ in Angkola Batak language. The theory used in this paper was the theory of Comparative Historical Linguistics which consists of two views, namely Types of Phonetic Changes and Types of Phonological Processes. The method used by the author was a comparative method between the Toba Batak language and the Angkola Batak language with a focused on the phoneme changes /b/ to /p/ and /d/ to /t/ in both languages. Based on the analysis described in the discussion chapter, it can be concluded that the consonant reflection phonemes /b/ and /d/ in Toba Batak language undergo linear changed to /p/ and /t/ in Angkola Batak language in the initial, middle and final positions. The changing included b > p and d > t, the changed occured consistently in the initial, middle and the final positions